Effects of mulch films with different thicknesses on the microbial community of tobacco rhizosphere soil in Yunnan laterite - Wang, Shuaibing; Li, Qiuping; Ye, Changbing; Ma, Wenqing; Sun, Yandong; Zhao, Bin; Zeng, Weiqing; Yue, Zhiqiang; Li, Lan; Li, Dandan (Frontiers in microbiology, 2024)
The mulch film (MF) management model of the agricultural field affects the physical and chemical properties of soil (PCPS) and the structure of the microorganism community; however, studies on the relationship between the rhizosphere microorganism community structure and the thickness of MF are still limited. To understand the interactions among the MF thickness, PCPS, and rhizosphere microorganism, a study was conducted by using an integrated metagenomic strategy, where tobacco rhizosphere soil was treated with four commonly representative and used thicknesses of MFs (0.004, 0.006, 0.008, and 0.010 mm) in Yunnan laterite. The results showed that agronomic traits such as the tobacco plant height (TPH), leaf number (LN), fresh leaf weight (FLW), and dry leaf weight (DLW) were significantly ( p < 0.01) improved in the field mulched with the thickest film (0.010 mm) compared with the exposed field (CK), and there was a 6.81 and 5.54% increase in the FLW and TPH, separately. The correlation analyses revealed a significant positive correlation of the MF thickness with the soil water content (SWC), soil organic matter (SOM), total nitrogen (TN), available nitrogen (AN), total phosphorus (TP), and available phosphorus (AP; all p < 0.01), while the MF thickness was negatively correlated with the soil temperature (ST; p < 0.01). In addition, the community structure of the rhizosphere soil bacteria was significantly changed overall by the MF thickness, which also interfered with the function of the rhizosphere soil bacteria. The correlation analyses also showed that the abundance of Bradyrhizobium and Nitrospira was positively correlated with the MF thickness, while the abundance of Sphinsinomonas and Massilia was negatively correlated with it. This indicated that with the increase of the MF thickness, the ability of the rhizosphere soil to utilize N and remove harmful molecules was strengthened, while the capacity of the rhizosphere soil to degrade pollutants was greatly reduced. These findings provide additional insights into the potential risks of the application of different thicknesses of MFs, particularly concerning the PCPS and soil microbial communities.